Oxytoc1n effectiveness in the time of delivery and prevention of bleeding after birth - Lourdes Arencio Heredia (2019)
This study tries to determine the efficacy of expectant management plus preventive oxytocin versus physiological management on the time for delivery and blood loss in post partum.An experimental groups and a control groups were randomly formed. Each one had 40 pregnant women.Collected data were processed and analyzed . It is shown that expectant management plus preventive oxytocin is more efficient since delivery tine is reduced in 07. 40 minutes . This difference was confirmed by t test which showed a significant difference in time for third phase of labor favoring experimental group . The significance level was 0.05